0831 Identifying Sleep-Related Breathing Disorders in Underserved Demographics Using Commercial Portable Monitoring Devices: A Case Report. (25th May 2022) - Tchopev, Zahari; Carrizales, Alex; Cunico, Jorey; Mysliwiec, Vincent; Peterson, Alan; Kim, David; Hansen, Shana; Powell, Tyler; Brock, Matthew
Abstract: Introduction: An estimated twenty-five percent of American women are at high risk of having obstructive sleep apnea (OSA). However, male sex is the predominantly reported risk factor. Women are less likely to report "classic" symptoms such as snoring that prompt referral for sleep evaluation. This dichotomy potentially represents a disparity in clinical evaluation and treatment of OSA in women. Consumer digital health devices are frequently used to monitor sleep in people with and without sleep disturbances. They are generally highly sensitive yet have lower specificity when compared with formal actigraphy or polysomnography. They may be used in conjunction with physician evaluation to guide decision-making. Report of Cases: A 33 year-old female with a pertinent past medical history of obesity (BMI 37.83 kg/m ), depression, chronic pain, and anxiety was referred to our sleep center with a multi-year history of excessive daytime fatigue and non-restorative sleep that persisted despite healthy habits counseling and unremarkable lab evaluation. She ultimately presented her primary care physician with biometric data collected by her Garmin watch and Oura ring. This data, which included a reported low SpO of 83%, motivated a referral to Sleep Medicine. Her presentation Epworth Sleepiness Scale (ESS) score and Insomnia Severity Index (ISI) were 14 and 17, respectively. Polysomnography revealed an AHI of 32.6/hr, oxygen nadir of 79%, ODI of 28.7/hr, and a 97.2% sleep efficiency. PLMS index was 23.2/hour but did not contribute to sleep fragmentation and there was increased proportion of stage N3 sleep (28.2%). Severe OSA was treated with APAP. The two month follow-up ESS and ISS improved to 9 and 4, respectively. Device data revealed greater than 6 hours of consistent nightly use with a residual AHI of 3.1/hr. She subjectively stated APAP "has been a life changer" personally and professionally, as well as spousal report of resolution of snoring. Her consumer devices similarly reported improved sleep measures. Conclusion: Minorities and women may be underserved in evaluation, diagnosis, and treatment of OSA. Portable monitoring using readily available consumer biometric devices may be a viable strategy for patients to further identify high risk features and prompt referral by primary care. Support (If Any): This work was supported by the Defense Health Agency, Defense Medical Research and Development Program, Clinical Research Intramural Initiative for Military Women's Health (DM170708; Mysliwiec) and the Air Force Research Laboratory, Wright Patterson Air Force Base, Ohio (FA8650-18-2-6953; Peterson).